(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2025)
A true public health emergency has resulted from the exponential increase in the prevalence of allergic diseases since the middle of the 20th century, which has also greatly advanced research into the underlying mechanisms and possible cures. The biological revolution has improved the treatment of allergic diseases by providing a variety of new immunomodulatory therapeutic and research tools that target the factors that contribute to allergic inflammation at separate pathophysiological processes. Notable examples include small-molecule modifiers of signal transduction, which are primarily mediated by Janus kinases and Bruton’s tyrosine kinases, as well as therapeutic monoclonal antibodies against cytokines, alarmins, and their receptors. Nevertheless, the primary treatment options have not yet transitioned from symptomatic to disease-modifying measures.In light of our current knowledge of allergy pathophysiology, we provide an overview of the medications currently on the market, suggest possible therapeutic targets, and wrap up by listing a few candidate immunopharmacological molecules that are being researched for possible future application in allergic diseases.